An appreciative inquiry approach to forum theatre on addressing ethnic prejudice for the Hillbrow Community Theatre Group - Bhebhe, Sibongile (My University, 2014)
This Practice as Research report investigates the syncretization of Forum theatre with Appreciative Inquiry in dealing with ethnic prejudice in Hillbrow, South Africa. The study looks at how two seemingly contradictory methods that, nonetheless, speak to each other can be merged. Appreciative Inquiry, a non-theatrical method, has been used to enhance Forum theatre, a theatrical method. The study argues that Appreciative Inquiry through its asset-based approach can enhance the problem-solving approach of Forum theatre to help participants address issues of identity, difference and diversity that largely speak to ethnic prejudice. The Research Report consisted of a Practice-based Research Project. This report focuses on the learning derived from the project. Chapter 1 looks at the background to the study, the aim, research question, rationale and the literature that informs it. In chapter 2 the theories of Appreciative Inquiry and the Theatre of the Oppressed are addressed. Chapter 3 looks at the conceptual framework of syncretizing Forum theatre with Appreciative Inquiry. Chapter 4 is the beginning of the analysis chapters where the matter of facilitation in the merged methods is addressed. Chapter 5 takes closer look at spect-acting in Syncretized Forum theatre. The matters of facilitation and spect-acting are further addressed in chapter 6 through the articulation of storytelling and folktale. Chapter 7 concludes the study. This Research Report asserts that the merging of the two methods had the ability to engage the participants in problem-solving in a more positive way in dealing with ethnic prejudice. The study raised questions about the efficacy of the positive principle of Appreciative Inquiry and the problem-posing approach of Forum theatre. The demanding nature of ethnic prejudice challenged the positive principle advocated by Appreciative Inquiry and the problem-posing approach of Forum theatre. It concludes that there is more work to be done in articulating the merging of the two methods.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Dramatic Art, 2013